Land Leasing And Land Sale As An Infrastructure-Financing Option - Peterson, George E. (The World Bank, 2006)
Municipal land sales provide one option for financing urban infrastructure investment. In countries where land is owned by the public sector, land is by far the most valuable asset on the municipal balance sheet. Selling land or long-term leasing rights to land use while investing the proceeds in infrastructure facilities can be viewed as a type of portfolio asset adjustment. This paper shows that in China many municipalities have financed more than half of their high rates of infrastructure investment from land sales, for periods of 10 to 15 years. Much of the remaining investment has been financed by municipal borrowing against the collateral of land values. Other countries also have turned to land sales and leasing for infrastructure finance. From a local perspective, land sales have the advantage that they typically are free from the intergovernmental restrictions that require higher-level approval for increases in local tax rates or user fees and that restrict local government borrowing. However, financing municipal infrastructure investment through land sales creates special risks that are not recognized in most intergovernmental fiscal frameworks. One danger involves the use of proceeds to finance operating budgets. Risk exposure is exaggerated by the highly volatile nature of urban land markets and evidence that in some countries urban land values in 2006 reflected a real estate bubble. In the past, Hong Kong, a jurisdiction that has relied heavily on land-leasing to finance its infrastructure budget, has seen land sales fall to zero at the bottom of the real estate cycle. The greatest financial sector risk stems from municipal borrowing based on inflated land values offered as collateral to banks. Sound intergovernmental fiscal management will require tighter regulation of municipalities' financial leveraging of land assets to avoid excessive risk taking by local governments